1992
DOI: 10.1002/1520-6807(199204)29:2<131::aid-pits2310290207>3.0.co;2-i
|View full text |Cite
|
Sign up to set email alerts
|

Social maladjustment and emotional disturbance: Problems and positions I

Abstract: Several controversies continue to surround the differentiation between the socially maladjusted (SM) and seriously emotionally disturbed (SED). Central to the controversy is the interpretation of social maladjustment. At one extreme, some restrict the definition of SM to include (a) the socialized aggressive and (b) adjudicated delinquents. At the other extreme, SM is construed broadly and includes (a) Conduct Disorder (group type, solitary aggressive, and undifferentiated), (b) Oppositional Defiant Disorder, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

1995
1995
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…However, only one of the five empirically based criteria (frequency) identified by Clarizio (1990) was ranked in the top five (third) in the current study. Further research is needed to determine whether those school psychologists who consider empirically based criteria more important are able to assess the severity of behavior disorders more accurately.…”
Section: Resultsmentioning
confidence: 70%
See 1 more Smart Citation
“…However, only one of the five empirically based criteria (frequency) identified by Clarizio (1990) was ranked in the top five (third) in the current study. Further research is needed to determine whether those school psychologists who consider empirically based criteria more important are able to assess the severity of behavior disorders more accurately.…”
Section: Resultsmentioning
confidence: 70%
“…Of the 1 1 criteria, 5 were empirically based and 6 were clinically based. Clarizio (1990) previously identified 5 criteria that research has shown to be important in evaluating the severity of depression, attention deficit hyperactivity disorder, and conduct disorder in children (i.e., related to current and/or future adjustment). The subjects were not aware that these criteria were dichotomized, however.…”
Section: Methodsmentioning
confidence: 99%
“…An early lie is a predictor of crime and other forms of maladjustment occurring in adulthood (Stouthamer-Loeber, 1986). In adolescents, lying is strongly correlated with other behavioral disorders such as: brawls, thefts, truancy, home escape, arson, vandalism, drinking, smoking, and drug use (Stouthamer-Loeber, 1986;McGhee & Short, 1991;Clarizio, 1992aClarizio, , 1992b. It is considered a symptom of social maladjustment (Pytka, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…We published the article in the context of a need to operational criteria for special education definitions and in the hope of addressing the nagging concerns related to who was and who should be receiving services for emotional disturbance, and the potential stigma associated with being labeled (cf. Clarizio, 1992; Forness, 1992a, 1992b, 1996; Kauffman & Badar, 2013; Mercer, Forgnone, & Wolking, 1978; Olympia et al, 2004; Yard, 1977; Ysseldyke, Algozzine, & Thurlow, 1982). My interest in definitions grew from my experiences teaching “educable mentally retarded,” “disabled reader,” and “emotionally disturbed” (as they were known at that time) students.…”
mentioning
confidence: 99%